Dimensionamento de estruturas de aço constituídas por perfis formados a frio em situação de incêndio - Claudio Henrique Soares (2002)
In this work the problem of the stability is analyzed and criteria are presented for the design of the resistance of cold-formed steel in fire conditions, still implementing a specific software for the design of the bars. For the implementation of the software design in high temperature the design philosophy was method adopted by NBR 14323 - Dimensionamento de estruturas de aço de edifícios em situação de incêndio and the prescriptions of NBR 14762 - Dimensionamento deestruturas de aço constituídas por perfis formados a frio. The implemented software embraces a variety of cold-formed profiles submitted to several types of efforts, according to the method of the limits states. Starting from the confrontation of the results obtained with studies accomplished in other countries it was verified that the implementation was done in a correct and efficient way. The obtained software can aid in the project of structures of cold-formed profiles, in fire conditions and room temperature, making possible a design rational, automatic and safe.